The Primary Health Center Factors Associated with Contraceptive Use Among Women in Indonesia - Arini Hardianti; Siswanto Agus Wilopo; Mohammad Hakimi; Althaf Setiawan (Alma Ata University Press, 2020)
Access to health care, especially health care’s days open was one of the important poin to increasing contraceptive user. Many people who want to use contraception tend to want to get the method in the same day when visited the health care. The aim of this study is to find the relationship health care days open and contraceptive utilization. The cross-sectional study used Performance Monitoring and Accountability (PMA) 2020 data in 33 provinces of Indonesia in 2015. The research subjects were primary health care (Puskesmas). In this research, a number of districts were merged to reach a minimum number of respondents of 30 women. One hundred and four health center were studied and analyzed with t-test and correlation, and multivariable analysis by looking at the level of significance p <0.05, and multivariable analysis. Female, household, and service delivery point questionnaire were used in this study. Result: All health centers in 76% area in Indonesia open more than five days a week and no stock out more than five contraceptive methods. All health centers in 69% area provides more than 5 methods. Days open statistically significant with modern contraceptive utilization after considering the stock out and method provides. Conclusion: contraceptive days open in health care generally good and have relation with contraceptive utilization after considers the stock and how many methods they provide.